A Refinement Approach to Design and Verification of On-Chip Communication Protocols - Boehm, P; Melham, T (2008)
Modern computer systems rely more and more on on-chip communication protocols to exchange data. To meet performance requirements these protocols have become highly complex, which usually makes their formal verification infeasible with reasonable time and effort. We present a new refinement approach to on-chip communication protocols that combines design and verification together, interleaving them hand-in-hand. Our modeling framework consists of design steps and design transformations formalized as finite state machines. Given a verified design step, transformations are used to extend the system with advanced features. A design transformation ensures that the extended design is correct if the previous system is correct. This approach is illustrated by an arbiter-based master-slave communication system inspired by the AMBA High-performance Bus architecture. Starting with a sequential protocol design, it is extended with pipelining and burst transfers. Transformations are generated from design constraints providing a basis for correctness-by-design of the derived system. ©2008 IEEE.